Development of a Digital Module Based on Local Wisdom of Balinese Folklore to Improve the Learning Outcomes of IPAS Students in Grade IV of Elementary School - Sumartini, Ni Wayan; I Nengah Suastika; Desak Putu Parmiti (Journal of Science and Education (JSE), 2026)
This development research aims to design and produce a digital module based on Balinese local wisdom of folklore on the ecosystem topic to improve IPAS learning outcomes of fourth-grade elementary school students that is valid, practical, and effective. The development model used in this study is the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The validity of the digital module was assessed by media experts and subject-matter experts using the Learning Object Review Instrument (LORI). Furthermore, practicality was evaluated through questionnaires distributed to teachers and students. The effectiveness test employed a pre-experimental design with a one-group pretest–posttest design. IPAS learning outcome data were collected using tests and analyzed using a one-tailed t-test. The results of the study reveal the following findings: (1) The design of the digital module based on Balinese local wisdom of folklore consists of a cover, preface, user guidelines, learning outcomes, learning objectives, concept map, ecosystem material integrated with Balinese folklore containing the values of Tri Hita Karana (Parhyangan, Pawongan, and Palemahan), unique fact columns,  summaries, instructional videos, practice questions, evaluations, references, and author profile. The module is presented as an interactive digital book developed using the Book Creator application, incorporating text, images, audio, video, and interactive evaluation links. (2) The results of media and material validity tests indicate that the average scores fall into the very valid category. (3) The practicality test results show that the digital module is categorized as very practical based on teacher and student responses. (4) The effectiveness test using a one-tailed t-test shows that the calculated t-value is greater than the t-table value, indicating that the use of the digital module based on Balinese local wisdom of folklore is effective in improving IPAS learning outcomes of fourth-grade elementary school students at SD Saraswati 4 Denpasar.